Multi‐Year Statistics of LEO Energetic Electrons as Observed by the Korean NextSat‐1. Issue 8 (17th August 2021) - Park, Jaeheung; Min, Kyoung Wook; Seo, Hoonkyu; Kim, Eo‐Jin; Ryu, Kwangsun; Sohn, Jongdae; Seon, Jongho; Yoo, Ji‐Hyeon; Lee, Seunguk; Kress, Brian; Lee, Junchan; Woo, Changho; et al.
Abstract: Monitoring the Earth's radiation belt by Low‐Earth‐Orbit (LEO) satellites has a long history and complemented observations near the high‐altitude equatorial plane. However, most of the previous LEO missions suffered from limitations in energy resolution, energy range, L ‐shell coverage, or the mission lifetime, which leave room for further improvement in this topic. For <80 keV electrons, the slot‐region outer edge at LEO moves inward with increasing geomagnetic activity, which agrees with previous Van Allen Probes reports. The behavior is more conspicuous for lower‐energy electrons. Latitudinal profiles of outer‐belt electron flux are smoother equatorward of the geosynchronous footprint latitudes (|MLAT| ∼ 66°) than poleward. The NextSat‐1 electron flux is positively correlated to geosynchronous observations, with the coefficient generally higher for higher electron energies. Also, both the geosynchronous and NextSat‐1 data exhibit similar spectral indices close to −3 in the log‐log space. All these results complement and expand previous knowledge on energetic electrons. The main findings are discussed in the context of existing literature. Plain Language Summary: The Earth's radiation belt consists of energetic particles which can potentially harm space assets and astronauts. Radiation belt science has a long history since the first discovery in the 1950s, and many of the unanswered questions were solved during the Van Allen Probes (VAP) era between 2012 and 2019. However, after the decommissioning of VAP, only a few spacecraft are continuously monitoring the radiation belt. In this study, we introduce the energetic electron data produced by a Korean Low‐Earth‐Orbit satellite, NextSat‐1. Since 2019, the satellite measures electron flux in the energy range between ∼30 keV and ∼2 MeV, at an altitude of 575 km and a local time of 22:30. We compare the data to geosynchronous GOES‐17 observations and find a good correlation between their daily variations (correlation coefficients > 0.6) and reasonable agreement in their power spectral index ranges (between −3.0 and −3.5). NextSat‐1 expands existing knowledge obtained from Medium‐Earth‐Orbit data, such as the inner edge of the outer radiation belt changing with geomagnetic activity and energy. We discuss those findings in the context of previous studies. Key Points: Energetic electron flux measured by Next‐Generation Small Satellite‐1 (NextSat‐1) exhibits a positive correlation to Geostationary Operational Environmental Satellite 17 observations, with the regression slope of 1 ∼ 2.5 The power spectral indices estimated from NextSat‐1 electron data conform to those of geosynchronous observations and with previous studies Even for the electrons near the loss cone edge, the slot‐region outer edge moves inward with increasing geomagnetic activity